Produktivitas dan Karkas Broiler yang Diberi Ransum Berbasis Tepung Daun Kasava dengan Penambahan Jintan Hitam (Nigellasativa) - N. Irwani; Riko Noviadi (Balitbangda Provinsi Lampung, 2017)
The experiment was done at the Cage Poultry Trial and Laboratory of Animal Husbandry, Departement of Animal Husbandry, the State of Politechnics of Lampung. The experiment began in July to September 2013. The experiment was conducted to determine the productivity and broiler carcasses using cassava leaves-based rationwithan addition of black cumin. The experiment was done in a Completely Randomized Design and tested for significance with a Duncan Multiple Range. Eighty four final stock CP 707 broiler chicks were used and the birds were placedrandomlyafter divided into 7 treatments and 4 replications. The treatments were R0 (without cassava leaf meal nor black cumin), R1 (7.5% cassava leaf meal only) R2 (7.5% cassava leaf meal + 1% black cumin), R3 (7.5% cassava leaf meal + 2% black cumin) R4 (15% cassava leaf meal only), R5 (15% cassava leaf meal + 1% blackcumin), and R6 (15% cassava leaf meal + 2% black cumin). Parameter measured were feedconsumtion, body weight gain and feed conversion ratio, carcass weight, and percentage of carcass weight. The result of this experiment showed that addition of 1% black cumin in adiet containing 7.5% cassava leaf meal improved the productivity and broiler carcass. Keywords: broiler chicks, cassava leaf meal, black cumin, productivity, carcass.